Differentiate (3x^2-5x)/(4x^3+2x^2)

We can differentiate the expression using the quotient rule. If f(x)=u(x)/v(x) then f'(x)=(u'(x)v(x)-u(x)v'(x))/v(x)^2. In this case u(x)=3x^2-5x so u'(x)=6x-5 and v(x)=4x^3+2x^2 so v'(x)= 12x^2+4x. Using the quotient rule the full derivative is: (6x-5)(4x^3+2x^2)-(3x^2-5x)(12x^2+4x)/(4x^3+2x^2)^2

Answered by Andras Ivan A. Maths tutor

3883 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Express root(125^x)/5^(2x-1) in terms of 5^a where a is an expression in terms of x.


How can I recognise when to use a particular method for finding an integral?


What is the derivative of f(x)=sqrt(3x+2)=(3x+2)^(1/2)?


Complete the indefinite integral : ∫x lnx dx


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences